Ball milling assisted hydrothermal synthesis of ZrO2 nanopowders. Issue 4 (May 2015) - Duran, Cihangir; Sato, Kimiyasu; Hotta, Yuji; Göçmez, Hasan; Watari, Koji
Abstract: The formation of ZrO2 nanopowders under various hydrothermal conditions such as temperature, time, autoclave rotation speed, heating rate and particularly assistance of ball milling during reaction was investigated. Full ZrO2 formation (with monoclinic phase) from zirconium solution was completed at shorter times with increasing temperature such as after 4 h at 150 °C, 2 h at 175 °C and less than 2 h at 200 °C. Crystallite size increased from 2.9 to 4 nm with increasing reaction temperature from 125 °C to 200 °C, respectively. Ball milling assisted hydrothermal runs were performed to understand the effect of mechanical force on phase formation, crystallinity and particle size distribution. Monoclinic ZrO2 was formed in both milled and non-milled runs when zirconium solution was used. Mean particle size for the 2 M solution was measured to be 94 nm for the milled and 117 nm for the non-milled powders. However, when amorphous aqueous zirconia gels (precipitated at pH 5.8) were used, tetragonal phase was also formed in addition to monoclinic phase. Mean particle size was measured to be 0.7 μm ( d 90 ≅1.3 μm) for the milled and 7.9 μm ( d 90 ≅13 μm) for the non-milled powders. Ball milling during hydrothermal reactions of both zirconium solution and aqueous zirconium gel resulted in smaller crystallite size and mean particle size and, at the same time, effectively controlled particle size distribution (or agglomeration) of nanopowders.